Probiotic potential and safety properties of Limosilactobacillus fermentum A51 with high exopolysaccharide production - Wei, Guangqiang; Wang, Daodian; Wang, Teng; Wang, Gao; Chai, Yunmei; Li, Yufang; Mei, Minhui; Wang, Hao; Huang, Aixiang (Frontiers in Microbiology, 2025)
IntroductionExopolysaccharides (EPS) produced by Lactic acid bacteria have many health benefits and unique physicochemical properties. They are widely used in the food industry to improve viscosity, mouthfeel, and textural properties of foods. In our previous studies, Limosilactobacillus fermentum A51 (L. fermentum A51) isolated from yak yogurt exhibited high EPS production capacity and was applied to improve the texture of yogurt. In this study, whole genome sequencing analysis and corresponding in vitro assays were performed to investigate the probiotic potential and safety properties of L. fermentum A51.ResultsScanning electron microscopy (SEM) observed that L. fermentum strain A51 adhered into clusters and its colony exhibited the obvious silk drawing phenomenon. Whole genome mapping revealed that L. fermentum A51 genome is 2,188,538 bp, and with an average guanine and cytosine (GC) content of 51.28%. PGAAP annotation identified 2,152 protein-encoding genes and 58 rRNAs, 15 tRNAs, and 5 5sRNAs. Hemolysis and antibiotic resistance tests, combined with the analysis of genes involved in antibiotic resistance, virulence factor, and hemolysins, suggested that L. fermentum A51 is safe. Fifty-one carbohydrate active enzyme genes in the whole genome sequence of L. fermentum A51 were annotated by carbohydrate active enzymes (CAZymes). Furthermore, L. fermentum A51 possesses adhesion, acid tolerance, bile salt tolerance, and heat tolerance genes (srtA, tuf, Bsh, nhaC, Ntn, cfa), antioxidant (nrfA, npr, nox2, tps), antibacterial genes (Idh and Dld) EPS synthesis-related genes (glf, epsG, gtf, Wzz, Wzx, Wzy), and signal molecule A1-2 synthesis-related genes (luxS, pfs). These probiotic genes were verified by quantitative real-time PCR. In vitro assays confirmed that L. fermentum A51 showed good tolerance to simulated gastrointestinal tract (8.49 log CFU/mL), 0.3% bile salt (39.06%), and possessed adhesion (86.92%), antioxidant (70.60–89.71%), and antimicrobial activities, as well as EPS and signaling molecule AI-2 synthesis capacities.ConclusionCollectively, our findings have confirmed that L. fermentum A51 is safe and exhibits good probiotic properties, thus recommending its potential application in the production of value-added fermented dairy products.